2021
DOI: 10.1002/andp.202100149
|View full text |Cite
|
Sign up to set email alerts
|

Broadband, High‐Efficiency and Wide‐Incident‐Angle Anomalous Reflection in Groove Metagratings

Abstract: In this paper, some nonplanar metagratings with multilevel asymmetric grooves are demonstrated to produce broadband and high‐efficiency anomalous reflection in wide‐incident‐angle range. First, bipartite metagrating with two asymmetric grooves per unit cell is proposed and optimized by machine learning. It can not only realize a high efficiency (≈88.8%) and large‐angle (≈70°) anomalous reflection under normal incidence, but also preserve the high performance over broad bandwidth (12.0–20.0 GHz) and wide‐incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition to the line current model, MGs based on traditional grating theory can also allow achieving energy distribution for two anomalous split beams. Similarly, it demands complex calculations and a genetic optimization algorithm. The groove-form unit cell also presents limitations in the polarization mode . In ref , dual-polarized MGs are realized through a mode matching the semi-analytical scheme.…”
Section: Introductionmentioning
confidence: 76%
“…In addition to the line current model, MGs based on traditional grating theory can also allow achieving energy distribution for two anomalous split beams. Similarly, it demands complex calculations and a genetic optimization algorithm. The groove-form unit cell also presents limitations in the polarization mode . In ref , dual-polarized MGs are realized through a mode matching the semi-analytical scheme.…”
Section: Introductionmentioning
confidence: 76%
“…The dependence of −1st-order diffraction efficiency on wave vectors is shown in figures 2(a) and (b) shows the details of the region of interest in (a). The white dotted line in figure 2 is the Rayleigh anomalies (RAs) [23,41] for diffraction orders, which can be calculated by the grating equation…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…Inampudi et al [72] recently demonstrated that the network architecture can enable a fast-paced inverse design of metagrating devices for a desired set of functionalities. A similar approach was recently employed by Liu et al to realize multifunctional metagratings [62] [see Fig. 10(b)].…”
Section: Metagratings Designed Based On Different Optimization Methodsmentioning
confidence: 99%
“…In recent years, there have been several studies proposing different designs for broadband metagratings [39], [61], [62]. There are two important issues that need to be considered when we talk about broadband metagratings.…”
Section: Broadband Multiband and Dual-polarized Metagratingsmentioning
confidence: 99%